Technology Of Physical Development Of Students With The Help Of Physical Education Means (Zien Journal of Social Sciences and Humanities, 2025)
This article discusses the processes of physical education of students based on the technology of physical development using physical education equipment and the techniques and means of physical training and fitness used in these processes